BAHASA DALAM KELUARGA MELAYU DI BANSIR DARAT, PONTIANAK - Violetta Oktafia Nanda (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2023)
In Indonesia there are several ethnic groups and national cultures. Management must be aware of the unique culture of each ethnic group in order to apply it more effectively and skillfully in the home environment. Malay culture and ethnicity, which is the largest ethnic group in Indonesia, is the focus of this study. The national cultural component is used to differentiate cultural variants among diverse ethnic groups. To form an effective family, communication is interaction that occurs in groups, especially in family interactions where a child is expected to understand and follow the directions of his parents. Similarly, parents must provide a good education to their children. In order to obtain data sources for this study, a family residing in Indonesia—specifically, West Kalimantan in Pontianak City—was interviewed and observed. This interview was conducted using particular questions on language and ethnicity. It is obvious that the responses to the questions will depend on how well the study subjects—namely, the two family members—understand them. Second, there is mutual understanding among Malay family members, wherein family members may mold personalities. These two factors together help produce a tranquil home atmosphere where children can be more readily overseen by parents in their growth. Third, communication between family members using Malay is done for harmony, with parents recognizing the problems and sentiments of children as well as parents' hectic schedules.